2016
DOI: 10.1002/14651858.cd011034.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and educational interventions for subfertile men and women

Abstract: The effects of psychological and educational interventions on mental health including distress, and live birth or ongoing pregnancy rates is uncertain due to the very low quality of the evidence. Existing trials of psychological and educational interventions for subfertility were generally poorly designed and executed, resulting in very serious risk of bias and serious inconsistency in study findings. There is a need for studies employing appropriate methodological techniques to investigate the benefits of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 75 publications
0
50
0
Order By: Relevance
“…A recent Cochrane review concluded that the effects of psychological and educational interventions on mental health of infertile women are uncertain due to the low quality of the existing evidence (Verkuijlen et al, ). In fact, only observational studies, non‐randomized trials, or small RCTs with high risk of bias have evaluated such interventions in the specific group of subfertile people (Feili et al, ; Galhardo et al, ; Li et al, ; Pascoe et al, ; Shahrestani et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Cochrane review concluded that the effects of psychological and educational interventions on mental health of infertile women are uncertain due to the low quality of the existing evidence (Verkuijlen et al, ). In fact, only observational studies, non‐randomized trials, or small RCTs with high risk of bias have evaluated such interventions in the specific group of subfertile people (Feili et al, ; Galhardo et al, ; Li et al, ; Pascoe et al, ; Shahrestani et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral and cognitive therapies have been used to reduce stress and mitigate its consequences in different populations, including infertile women (Verkuijlen, Verhaak, Nelen, Wilkinson, & Farquhar, ). Some of these therapies are based on the principle of mindfulness, defined as a meditation practice that cultivates present moment awareness (Crane et al, ; Ludwig & Kabat‐Zinn, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of 20 randomized controlled trials that examined the effects of psychosocial interventions on the pregnancy rates, mental health, and marital function of infertile couples, it was found that depression and stress were not relieved (Ying, Wu, & Loke, ). A Cochrane review of 39 studies revealed that psychological and educational interventions had effects on mental health, including distress, but live births or current pregnancy rates were uncertain because of the very low quality of evidence of the studies (Verkuijlen, Verhaak, Nelen, Wilkinson, & Farquhar, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the intervention group, there was a trend toward a higher rate of ongoing pregnancies (13/69 vs. 13/115) compared to the women in the standard treatment group (Chan et al, 2006). With only three studies reporting birth or pregnancy rates, a current Cochrane review concludes that the effects of psychological interventions for subfertile men and women are uncertain (Verkuijlen et al, 2016).…”
Section: Psychotherapeutic Interventions In Women With Infertilitymentioning
confidence: 99%